How forests survive alongside flammable open ecosystems: conservation implications for Africa - Cardoso, Anabelle Williamson; Beckett, Heath; Bond, William John (Frontiers in Conservation Science, 2023)
Mosaics of closed, fire-sensitive forests and open flammable ecosystems are common in many parts of the world. The open ecosystems have long been interpreted as products of deforestation, but diverse lines of evidence point to their origins millions of years before humans. There is widespread concern over the survival of fire-sensitive forest in a flammable matrix, leading to diverse measures, including fire suppression, to protect forests. But if both systems are ancient, how did fire-sensitive forests survive the regular fires in the flammable open ecosystems? Here we discuss recent research on this topic, including the stability of these mosaics through time and the factors accounting for this. These include local topography, variation in grass flammability, the presence of fire-tolerant forest margin tree species, and fauna that create firebreaks along the forest edge. We go on to discuss the conditions under which mosaics are less stable, for example during extreme fires, and consider the uncertain future of mosaicked landscapes under climate change. Finally, we suggest a set of guidelines for consideration by conservation managers concerned about fire damage to forest patches.